2013
DOI: 10.1002/hipo.22118
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal NMDA receptor blockade impairs CREB phosphorylation in amygdala after contextual fear conditioning

Abstract: In contextual fear conditioning (CFC), hippocampus is thought to process environmental stimuli into a configural representation of the context and send it to amygdala nuclei, which current evidences point to be the site of CS-US association and fear memory storage. If it is true, hippocampus should influence learning-induced plasticity in the amygdala nuclei after CFC acquisition. To test this, we infused wistar rats with saline or AP5, a NMDA receptor antagonist, in the dorsal hippocampus just before a CFC se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
1
18
0
1
Order By: Relevance
“…There is considerable evidence that the amygdala and hippocampus are anatomically connected to each other (Pitkanen et al ., ) and functionally interact during encoding of emotional memory (Richardson et al ., ; Calandreau et al ., ). It has been shown that intra‐DH infusion of muscarinic antagonists or NMDA receptor antagonists diminishes contextual fear conditioning‐induced phosphorylation of ERK1/2 or CREB in the BLA (Calandreau et al ., ; de Oliveira Coelho et al ., ). It has also been shown that a lesion in the DH disrupts the context specificity of extinction and impairs the context dependence of amygdala neuronal activity evoked by an extinguished conditioned stimulus (Ji and Maren, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence that the amygdala and hippocampus are anatomically connected to each other (Pitkanen et al ., ) and functionally interact during encoding of emotional memory (Richardson et al ., ; Calandreau et al ., ). It has been shown that intra‐DH infusion of muscarinic antagonists or NMDA receptor antagonists diminishes contextual fear conditioning‐induced phosphorylation of ERK1/2 or CREB in the BLA (Calandreau et al ., ; de Oliveira Coelho et al ., ). It has also been shown that a lesion in the DH disrupts the context specificity of extinction and impairs the context dependence of amygdala neuronal activity evoked by an extinguished conditioned stimulus (Ji and Maren, ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers and immediate-early gene expression induced by new types of learning conditions reflect similar asymmetric patterns of activation. For example, elevated levels of protein kinase C (PKC) or cyclic AMP response element binding protein (CREB) are integral components of the molecular cascades that convert new information from short, to long term memory (Zhou et al, 2009; de Oliveira Coelho et al, 2013; Pinho et al, 2013). Surprisingly both proteins are upregulated in the right, but not left amygdala after exposure to a tone previously paired with an aversive experience such as footshock during fear conditioning training or in response to exposure to a threatening predator (Blundell and Adamec, 2007; Orman and Stewart, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the HPC and amygdala are functionally connected as measured by local field potentials (LFPs) and within these regions neuroplasticity mechanisms are engaged during both contextual fear conditioning and expression (De Oliveira Coelho et al ; Huff & Rudy ; Lesting et al ; Maren & Hobin ; Trifilieff et al ). Although the roles of the BLA, CeA and dHPC have been well‐documented in contextual fear behavior, they are likely part of a larger neural circuit supporting contextual fear conditioning, as other structures are also necessary for the acquisition and expression of conditioned freezing.…”
mentioning
confidence: 99%